PENGARUH DESENTRALISASI FISKAL TERHADAP PENINGKATAN KASUS KORUPSI DI PEMERINTAH DAERAH - Waruwu, Malmingcer; Sumanto, Listyowati (Ensiklopedia of Journal, 2025)
Fiscal decentralization is a policy strategy that aims to strengthen regional independence in managing financial resources and bringing public services closer to the community. However, in practice, fiscal decentralization often raises new problems, one of which is the increasing potential for corruption at the local government level. This study examines the weaknesses of the supervisory system, lack of human resource capacity, and weak institutional integrity as factors that reinforce the negative relationship between fiscal decentralization and clean governance. This study aims to analyze how the delegation of fiscal authority from the central government to the regions affects the frequency and pattern of corruption in the local government environment. Using a type of descriptive normative juridical research, secondary data were analyzed qualitatively. Draw conclusions using deductive logic. The findings show that although fiscal decentralization brings positive potential in regional development, its implementation has not been accompanied by an adequate internal and external control system, thus increasing the scope for budget abuse. Therefore, it is necessary to strengthen supervisory policies, increase fiscal transparency, and empower civil society as social control. The study concludes that fiscal decentralization will only have a positive impact if it is accompanied by reform of the legal system, increased accountability, and integrity enforcement at the local level.  Keywords: Fiscal Decentralization, Corruption, Local Government, Supervision, Financial Governance